Secondary decompressive craniectomy after severe traumatic brain injury: a retrospective cohort study - Che, Wenwen; Feng, Cheng’ao; Xu, Xiaomei; Shen, Qiuyan; Rao, Jianwei; Wang, Yuhai (Frontiers in Neurology, 2025)
BackgroundSevere traumatic brain injury (sTBI) often results in malignant intracranial hypertension, requiring decompressive craniectomy (DC). Although guidelines emphasize adequate decompression, craniectomy size is often individualized in practice. Secondary DC may be necessary when initial decompression is insufficient. This study investigated the risk factors and outcomes associated with secondary DC in sTBI patients.MethodsWe conducted a retrospective cohort study of 101 sTBI patients who underwent DC between 2021 and 2023. Patients were divided into two groups: those receiving only primary DC (N = 85) and those requiring secondary DC (N = 16). Logistic regression identified predictors of secondary DC, while inverse probability of treatment weighting (IPTW) was applied to adjust for confounders.ResultsOf the 101 patients who underwent DC, 85 received primary DC alone, while 16 required secondary DC. Patients in the secondary DC group had lower admission GCS scores (6.06 ± 2.95 vs. 7.88 ± 3.48, p = 0.038), higher preoperative ICP (45.4 ± 18.5 mmHg vs. 30.3 ± 16.2 mmHg, p = 0.007), and smaller initial craniectomy areas (110 ± 31.5 cm2 vs. 133 ± 51.4 cm2, p = 0.024). Multivariable regression identified preoperative ICP (OR 1.06, 95% CI 1.00–1.11, p = 0.038) and craniectomy area (OR 0.98, 95% CI 0.96–1.00, p = 0.037) as independent predictors of secondary DC. IPTW-adjusted analyses showed no significant differences in functional outcomes or complication rates.ConclusionSecondary DC may serve as an effective salvage intervention in sTBI patients with refractory intracranial hypertension following primary DC. Although these patients present with more severe initial conditions, secondary DC did not increase the risk of complications or lead to poorer outcomes. Ensuring adequate decompression during the initial surgery may help reduce the need for secondary intervention.